Editorial - Souza, Alice De Marchi Pereira de; Mattos, Amana; Jacó Vilela, Ana Maria; Mendonça, Anderson Pereira; Ponciano, Edna Lúcia Tinoco; Degani-Carneiro, Filipe; Hernández, Jimena de Garay; Quadros, Laura Cristina de Toledo; Tura, Luiz Fernando; Brunhari, Marcos Vinicius; et al. (Estudos e Pesquisas em Psicologia, 2021)
Alice De Marchi Pereira de Souza, Amana Mattos, Ana Maria Jacó Vilela, Anderson Pereira Mendonça, Edna Lúcia Tinoco Ponciano, Filipe Degani-Carneiro, Jimena de Garay Hernández, Laura Cristina de Toledo Quadros, Luiz Fernando Tura, Marcos Vinicius Brunhari, Michelle Menezes Wendling, Patrícia Lorena Quitério, Rosana Lazaro Rapizo, Sabrina Dal Ongaro Savegnago, Vitor Castro Gomes